Challenges and strategies for management and conservation of water resources and freshwater biodiversity in the Lake Victoria Basin - Masese, Frank O.; Wanderi, Elizabeth W.; Nyangweso, Hyline N. (Frontiers in Conservation Science, 2025)
The Lake Victoria Basin (LVB) is an important economic growth zone, sustaining the livelihoods of more than 42 million people. The economies of the five countries in the LVB (Burundi, Kenya, Rwanda, Tanzania and Uganda) rely heavily on the rich array of natural resources and ecosystem services provided by the basin. However, significant alterations of terrestrial and aquatic ecosystems have occurred over the past century. This human-led transformation is evident in the areal reduction of native vegetation and wetlands, giving way to expanding agriculture and human settlements. Human activities have further manifested in observable declines in water quality, unregulated water abstractions, eutrophication, infestation of exotic and invasive species, dwindling fisheries, and biodiversity declines. These challenges are exacerbated by growing conflicts over resource access and use, and shortcomings in policies, laws, and institutional structures, posing unsustainable threats to ecosystem vitality and resilience. To address these multifaceted challenges, comprehensive management strategies are essential for the well-being of future generations. This paper critically reviews existing literature, elucidating the primary human impacts and threats jeopardizing water resource sustainability and biodiversity conservation in the LVB. It also proposes corresponding management measures to either be implemented or enhanced, aiming to counteract the ongoing degradation of natural resources and safeguard biodiversity. Coordinated management actions at the river catchment and regional scales are imperative, operating within the frameworks of regional cooperation. Priority should be accorded to a cohesive Integrated Water Resources Management (IWRM) approach, reinforced by harmonized regional laws and regulations. Emphasizing participatory approaches through co-management, enhanced gathering and dissemination of research findings, mainstreaming climate change considerations, implementing sustainable environmental monitoring protocols, and introducing novel strategies like Payment for Ecosystem Services (PES) are crucial steps to reduce reliance on donor funds. The paper also underscores the need for additional research to bridge existing knowledge gaps concerning the status of water resources and biodiversity conservation in the region.